Antenna performance enhancement with Artificial Magnetic Conductor(AMC) - Dewan, R. (Institute of Electrical and Electronics Engineers Inc., 2016)
Artificial Magnetic Conductor (AMC) is a metamaterial which is widely used nowadays in antenna designs. AMC mimics the behavior of Perfect Magnetic Conductor (PMC) which is not available in nature. With the incorporation of AMC to antenna designs, various performance of the antenna can be improved. In this paper, AMC application in antenna design is presented for key areas of transmission enhancement between antennas, RFID detection ranges and frequency reconfigurable antenna.